Competition in Markets for Credence Goods - Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
This paper investigates the functioning of markets for credence goods. These are markets in which the information asymmetries are of the form that sellers are also experts who determine customers' needs. It examines the role of customers' search for multiple opinions in disciplining experts. It characterizes the equilibrium amount of fraud in such markets and shows that, despite intense competition, the information asymmetry will be translated into a mark-up over cost embodied in the prices of the less expensive services. It points out that the equilbrium does not maximize the expected customers' surplus, even subject to the informational constraints regarding the experts' superior information.
Keywords: 330